Stress Distortion Restraint to Boost the Sodium Ion Storage Performance of a Novel Binary Hexacyanoferrate. Issue 4 (11th December 2019) - Li, Weijie; Han, Chao; Wang, Wanlin; Xia, Qingbing; Chou, Shulei; Gu, Qinfen; Johannessen, Bernt; Liu, HuaKun; Dou, Shixue
Abstract: Mn‐based hexacyanoferrate Na x MnFe(CN)6 (NMHFC) has been attracting more attention as a promising cathode material for sodium ion storage owing to its low cost, environmental friendliness, and its high voltage plateau of 3.6 V, which comes from the Mn 2+ /Mn 3+ redox couple. In particular, the Na‐rich NMHFC ( x > 1.40) with trigonal phase is considered an attractive candidate due to its large capacity of ≈130 mAh g −1, delivering high energy density. Its unstable cycle life, however, is holding back its practical application due to the dissolution of Mn 2+ and the trigonal‐cubic phase transition during the charge–discharge process. Here, a novel hexacyanoferrate (Na1.60 Mn0.833 Fe0.167 [Fe(CN)6 ], NMFHFC‐1) with Na‐rich cubic structure and dual‐metal active redox couples is developed for the first time. Through multiple structural modulation, the stress distortion is minimized by restraining Mn 2+ dissolution and the trigonal‐cubic phase transition, which are common issues in manganese‐based hexacyanoferrate. Moreover, NMFHFC‐1 simultaneously retains an abundance of Na ions in the framework. As a result, Na1.60 Mn0.833 Fe0.167 [Fe(CN)6 ] electrode delivers high energy density (436 Wh kg −1 ) and excellent cycle life (80.2% capacity retention over 300 cycles), paving the way for the development of novel commercial cathode materials for sodium ion storage. Abstract : A novel binary hexacyanoferrate (Na1.60 Mn0.833 Fe0.167 [Fe(CN)6 ], NMFHFC‐1) with a Na‐rich and cubic structure is developed for the first time. Through multiple structural modulation, the stress distortion is minimized by restraining Mn 2+ dissolution and the trigonal‐cubic phase transition. Moreover, NMFHFC‐1 simultaneously retains Na ions in its framework. As a result, the NMFHFC‐1 electrode delivers high energy density and excellent cycle life.